Essential notes on applied energy : for mechanical and chemical engineering students (objective, practical short questions & sample answers) - Mohammad Omar, Abdullah (Universiti Malaysia Sarawak, 2012)
Applied energy refers to any energy conversion when applied to energy systems which include energy conversion and conservation, energy resources and sustainability, energy processes and environment applications analysis.